Implementation of the Five Methods in Tahsin Activities at the Qur'an House Rabbani - Aulia Hudamahya; Amelisa Putri; Rapi Pernandes; Raihan Ramadhani; Ikhwan Rahman; Meni Veradegita (International Journal of Multidisciplinary Research of Higher Education, 2022)
This study aims to explore how the tahsin education method for children in the Quran House Rabbani institution. This study used a qualitative method with an ethnographic approach, research data were taken through direct interviews with five informants (teachers of the Quran House Rabbani). All interview and observation data were then analyzed thematically using a model Miles and Huberman. Overall, the results of the analysis show that there are five tahsin methods in the Rabbani Qur'anic House. The five methods are: i) talaqqi, ii) Muraja’ah, iii) recitations, iv) huffazh, v) talqin. The results of this study can be used as initial data for subsequent researchers in studying different issues related to this problem and various other issues that are relevant to this context